Therapeutic Tactics in patients with Polypous Rhinosinuitis, depending on the Morphological Picture of the Nasal Cavity - Kurbanov Elmurod Xushvaktovich; Eshkobilova Surayo Turaevna (Central Asian Journal of Medical and Natural Science, 2021)
Chronic polyposis rhinosinusitis (CPMS) is a multifactorial polyetiological disease [1].The problem of nasal polyps and paranasal sinuses remains relevant, since the main aspects of this pathology (etiological, pathogenetic, immunological, therapeutic) have not been fully resolved all over the world. The disease is accompanied by a decrease in the patient's quality of life. According to the latest position papers on rhinosinusitis and nasal polyps of the European Academy of Allergology and Clinical Immunologe (EAACI Position Paper on Rhinosinusitis and Nasal Polyps - EPOS, 2007; 2012), the prevalence of CPMS in the population ranges from 1 to 4% , while men get sick more often [2]. The disease often occurs in people of working age at the age of 25-35. Nasal polyps are a manifestation of the so-called special form of chronic rhinosinusitis, caused by a bacterial or fungal infection, with the formation of chronic eosinophilic inflammation.